Eksplorasi Strategi Pengembangan Ekonomi Kreatif Berbasis Pariwisata dalam Meningkatkan Daya Saing Daerah Kabupaten Barru - Ashey Yuniar; Magfiratul Jannah; Irma Irma; Moh. Taufik Saidul Akbar; Dewi Kurnia (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to explore creative economy development strategies based on tourism to improve the competitiveness of Barru Regency. The approach used is descriptive qualitative with exploratory and conceptual methods through secondary data analysis, literature studies, policy documentation, and indirect observation of regional creative economy and tourism development. The results show that Barru Regency has strong creative economy potential in the sub-sectors of performing arts, local cuisine, handicrafts, and tourism services that are integrated with cultural wealth and natural resources. Effective development strategies include strengthening destination-based creative economy clusters, empowering local communities, increasing human resource capacity, innovating creative products, and strengthening branding and market access. Tourism-based creative economy development also has positive implications for increasing community income, preserving local culture, strengthening regional institutions, and the sustainability of sharia-based economic development. This study confirms that tourism-based creative economy can be a strategic instrument in strengthening the region's sustainable competitiveness in Barru Regency.